Comparison of Students Science Literacy Abilities Using Inquiry and Cooperative Learning Models - Panjaitan, Muktar Bahruddin; Siagian, Asister Fernando; Judijanto, Loso; Mufarizuddin, Mufarizuddin; Herman, Herman; Saputra, Nanda; Mamadiyarov, Zokir (Pandawan, 2026)
The purpose of this study was to determine whether there is a difference in scientific literacy between students who follow the inquiry learning model and students who follow the STAD cooperative learning model to determine the difference between scientific literacy due to students' achievement motivation to describe the interaction between the learning model and achievement motivation on students' scientific literacy. This study used a Posttest-Only Control Group Design with a two-factor analysis. The population in this study were fifth-semester PGSD students at HKBP Nommensen University of Pematangsiantar, in 2024/2025 Academic Year, with totaling 186 students, which sample of 124 students determined by using Simple Random Sampling technique for the class. Data were obtained using the achievement motivation instrument and the science literacy test. Data analysis was carried out using two-way analysis of variance. The study found a significant difference in scientific literacy between students who followed the Inquiry Learning Model and those who followed the STAD Cooperative Learning Model, with a p-value of 0.000, which is less than 0.05. There is a difference in student science literacy based on achievement motivation with a value of Sig. 0.000 < 0.05 and there is no interaction between the learning model and achievement motivation on student science literacy, with a value of Sig. 0.230 > 0.05.